Interaction of Mitoxantrone-Loaded Cholesterol Modified Pullulan Nanoparticles with Human Serum Albumin and Effect on Drug Release. (16th May 2019) - Yuan, Liming; Guo, Bu; Zhong, Wu; Nie, Yu; Yao, Xiaoyan; Peng, Xiaofeng; Wang, Rong; Yu, Hongyuan; Yang, Shanyi; He, Chunlian; Tao, Xiaojun; Zhang, Qiufang
Abstract : To clarify nanoparticle-protein interaction and their action characteristics, the interactions between MTO-CHP NPs and human serum albumin (HSA) were studied by isothermal titration calorimetry (ITC), fluorescence spectroscopy, dynamic light scattering (DLS), and circular dichroism spectroscopy (CD). Hydrophobically modified pullulan (CHP) nanoparticles (NPs) loaded with mitoxantrone (MTO) were prepared (MTO-CHP NPs) with size 166.9 nm. The spherical shape was verified by transmission electron microscopy (TEM). The ITC results demonstrated an interaction between MTO-CHP NPs mainly by hydrophobic interaction force, electrostatic force, and hydrogen bonding. The mean binding constantK A was0.832 × 10 4   M − 1 and mean HSA coverage0.939 ± 0.302 . MTO-CHP NPs could quench the fluorescence intensity of HSA, which gradually decreased to be balanced in 9 h and indicated the completion of the complexation. The size and zeta potential changes of the combined particle were dynamically detected with DLS at 0, 3, 6, 9, 12, 15, and 18 h. When the reaction was completed at 9 h, the particle size and potential remained stable, accompanied by a size change from 89.91 to about 145 nm and potential change from -15 to -3 mV, respectively. The results of CD measurement showed that the change in ellipticity of HSA at 208 nm was similar to the fluorescence spectra and DLS measurements with MTO-CHP NPs combined with HSA. At the beginning of the reaction, the proportion of α -helix was 52.3% to 43.7%, which decreased by 39.1% at compound stabilization. The release of MTO from MTO-CHP NPs atpH = 5.6 was significantly accelerated, whereas that of MTO from HSA-MTO-CHP NPs was significantly reduced, and the drug release was significantly slowed down even under acidic conditions, which indicates the beneficial effect of HSA on the persistence and stability of the HSA-MTO-CHP NP compound.